Implementasi Strategi Pembelajaran Small Group Discussion dalam Meningkatkan Pemahaman Siswa pada Mata Pelajaran Fikih di Madrasah Aliyah Miftahul Ulum Bettet Pamekasan - Hefni; Atnawi (Indo-MathEdu Intellectuals Journal, 2026)
Student comprehension in Fiqh (Islamic jurisprudence) lessons requires instructional strategies that foster active engagement and interaction. This study aims to describe the implementation of the Small Group Discussion (SGD) strategy to enhance student understanding and to identify the factors supporting or hindering its application in Fiqh classes at Madrasah Aliyah Miftahul Ulum Bettet, Pamekasan. A qualitative descriptive approach was employed, with data collected through interviews, observations, and document analysis involving the school principal, the Fiqh teacher, and students. Data analysis proceeded through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the Small Group Discussion strategy encourages student engagement and supports comprehension of Fiqh material. Supporting factors include student enthusiasm, a comfortable learning atmosphere, increased motivation, and the availability of adequate learning facilities and media. Conversely, hindering factors include a lack of awareness among some students regarding the importance of formal education and fatigue during lessons. Thus, the Small Group Discussion strategy serves as a viable alternative instructional method to support student understanding in Fiqh subjects.